The relationship between academic performance and parent-school interactions in schools: A multi-country perspective from the 2015 PISA round - Alinsunurin, Jason P. (Animo Repository, 2021)
The empirical literature connecting parental involvement with academic performance in mathematics, sciences, and reading is one of the most contentious in education policy debates. Homebased parental involvement, or the role of parenting and the family in ensuring a supportive and conducive learning climate, has been known to relate to academic performance positively. Still, a generalizable connection between parent-teacher interactions and academic achievement remains less understood and nuanced. Using more than 76,000 responses from 12 countries, we econometrically show that parents’ interactions with teachers within school settings are more common among parents of students who have lower performance, regardless of the initiator. This finding infers that decreased academic performance are crucial mechanisms of school-to-home involvement, contrasting with prior literature where home-based parental involvement has direct pathways to improve academic achievement. We also find different score thresholds exist depending on the country and the educational area, which reflects the social and cultural differences in parental involvement conventions. Our study further confirms the existence of vast gaps in academic performance among students’ gender, socioeconomic, and ethnolinguistic backgrounds.